Westminster Abbey: a church in history - Cannadine, David (Paul Mellon Centre for Studies in British Art in association with The Dean and Chapter of the Collegiate Church of St Peter Westminster (Westminster Abbey), 2019)
Westminster Abbey was one of the most powerful churches in Catholic Christendom before transforming into a Protestant icon of British national and imperial identity. Celebrating the 750th anniversary of the consecration of the current Abbey church building, this book features engaging essays by a group of distinguished scholars that focus on different, yet often overlapping, aspects of the Abbey’s history: its architecture and monuments; its Catholic monks and Protestant clergy; its place in religious and political revolutions; its relationship to the monarchy and royal court; its estates and educational endeavors; its congregations; and its tourists. Clearly written and wide-ranging in scope, this generously illustrated volume is a fascinating exploration of Westminster Abbey’s thousand-year history and its meaning, significance, and impact within society both in Britain and beyond.